Influence of immunosuppression on morphostructure of the epididymis in experimental animals in the period of pronounced senile changes - S. A. Kashchenko; A. A. Zakharov (Сеченовский вестник, 2018)
Infertility issues, regarded as an important component of modern medicine, which are, at the same time, a significant public problem, are becoming relevant for the elderly due to the increase in the average life expectancy. Alongside with that, in recent years, the negative impact of a complex of anthropogenic and environmental factors on the state of human health has been intensifying, which is especially important for the industrialized regions, including the Donbass. It has been proved that external influences, including the use of a complex of various medications, cause a typical response of the body, manifesting as systemic immunosuppression. The state of this issue prescribes the purpose of the study: the establishment in the experiment of morphogenesis of specific features of the epididymis in animals’ testes in the period of pronounced senile changes under conditions of prolonged systemic immunosuppression. The study was carried out on 60 white rats in the period of pronounced senile changes. The state of immunosuppression was modeled by the use of an alkylating cytostatic cyclophosphamide at a dosage of 1.5 mg/kg body weight intramuscularly for 10 days. The rats were taken out of the experiment by decapitation under ether anesthesia at 1, 7, 15, 30 and 60 days after the immunosuppressant was discontinued. In the epididymis of animals in the period of pronounced senile changes, a strong reaction is observed in response to prolonged systemic immunosuppression. Macromorphometric parameters of the organ undergo statistically significant changes in both early and late observation periods (7, 15 and 30 days), which indicates cumulative toxic and immunosuppressive effects of cyclophosphamide on the morphogenesis of epididymis. Changes in indicators at a microscopic level in the same period confirm the shifts in the organʼs body indicators, which confirms a disruption to its homeostasis caused by dysfunction of regulatory processes. The obtained results arouse interest in the study of the morphogenesis of the epididymis in conditions of acute immunosuppression in in relation to age.